Interest of the Sol‐Gel Approach for Multiscale Tailoring of Porous Bioelectrode Surfaces. Issue 3 (26th October 2012) - Côme, Yémima Bon Saint; Lalo, Hélène; Wang, Zhijie; Kohring, Gert‐Wieland; Hempelmann, Rolf; Etienne, Mathieu; Walcarius, Alain; Kuhn, Alexander
Abstract Gold nanoparticles have been co‐encapsulated with D‐sorbitol dehydrogenase and diaphorase in electrodeposited thin sol‐gel films. We demonstrate here that the nanoparticles allow improving significantly the catalytic efficiency of the bioelectrodes. The hybrid material was electrodeposited in the cavities of macroporous electrodes and characterized by high‐resolution transmission electron microscopy and electrochemistry. Well‐defined silica gel layers containing homogeneously dispersed nanoparticles were obtained, leading to high current densities in the presence of D‐sorbitol. The access to the internal porosity of the macroporous electrode was not hindered by the presence of the electrodeposited sol‐gel layer. In addition, a very significant enhancement factor, that describes the current increase with the increasing macroporous surface area was obtained due to the contribution of the tridimensional gold nanoparticle network.